Thai Koi-Hoi Snail Dish and Angiostrongyliasis Due to Angiostrongylus cantonensis: Effects of Food Flavoring and Alcoholic Drink on the Third-Stage Larvae in Infected Snail Meat - Eamsobhana, Praphathip; Yoolek, A.; Punthuprapasa, P.; Yong, Hoi Sen (Mary Ann Liebert, 2009)
Human infection with the rat lungworm Angiostrongylus cantonensis (Parastrongylus cantonensis) in Thailand, especially in the northeastern region, is associated with the habit of eating koi-hoi, which contains raw snail meat. Infection results from the snails being carriers of the larval parasite. The present study was conducted to assess the effect of food flavorings in koi-hoi, alcohol, and exposure time of the two variable on the infective larvae of A. cantonensis. Infected Biomphalaria glabrata snails were used for koi-hoi preparation. Raw snail meat was mixed with koi-hoi flavoring and left at room temperature for various time periods ranging from 5 to 60 minutes. At a predetermined time, two pieces of snail meat were removed at random and examined for viability (as determined by motility) of the parasitic third-stage larvae. At the same time, two random pieces of snail meat were removed and treated with 10 mL of a local 40% alcoholic drink for 30 minutes before examination of larval viability. Exposure of infected snail meat for 10 minutes or more to koi-hoi food flavoring resulted in significantly more nonmotile (dying or dead) larvae. Addition of the local alcoholic drink after exposure to the flavoring exerted an additional killing effect on the larvae. Despite long exposure time, both the koi-hoi flavoring and addition of alcoholic drink were not completely effective in killing the infective larvae in the snail meat. Thorough cooking of the food intended for human consumption should still be practiced.